Impact Assessment of Micro Finance Bank on Poverty Reduction in Kano State: A Case of Garko Local Government Area - Mzungweg, Agbir; Mailamba, Ishaya John; Yunana, Titus Wuyah (Annals of Human and Social Sciences, 2024)
The study examined the impact of microfinance banks on poverty reduction in Kano State, with particular focus on Garko Local Government Area, Microfinance and poverty has been a critical topic in the field of academic research. In recent years, microfinance institutions have gained significant attention as an effective tool for poverty alleviation. The the study used primary data generated from questionnaire administered to 290 sample size. The study uses logit regression model and examined the impact of microfinance banks on poverty reduction in Kano State. The findings show that all the variables (sex, educaltional level, income level, interest rate and loan size) are statistically significant in influencing poverty reduction in Garlo Local Government of Kano State while age is negatively related to poverty reduction and statistically insignificant. The study therefore recommends that, microfiance banks should expand the size of their loan to businesses, which will significantly improved the lives of the poor in the area. Micro finance banks should have a moderate interest rate that will encougare the poor and businesses to loan more fund for investment, increase income and reduce poverty.